Selaginella likabalika Aran & Roy sp. nov: a new species from Arunachal Pradesh, India - Aran, Khencha; Roy, Himu (Current Botany, 2023)
A new species of Selaginella i.e., Selaginella likabalika is described in the present study. The species was collected from Likabali, under the Lower Siang district and Karsingsa, under the Papumpare district of Arunachal Pradesh. The new species can be easily confused to be mosses due to their similar appearance and habitat resemblance. The species is minute, prostrate and generally covers the ground like a carpet. The morphology of the new species is close to Selaginella armata, S. apoda, S. confusa and S. flacca but can be differentiated by leaf features.